Building a digital twin for IoT smart stores: a case in retail and apparel industry. (22nd June 2021) - Maïzi, Yasmina; Bendavid, Ygal
Today, digital twins (DT) are among the highest technological trends and have moved from concept to reality. Although the first implementations were conducted in Industry 4.0, their evolution is expected to transform the face of several industries. Even though there has been a considerable growth of interest in DT concept, its application remains at a cradle stage and research in other sectors such as retail are very limited. Additionally, since an increasing number of companies are implementing internet of things (IoT) technologies, they may deploy a DT in the next years, and knowing realistic impacts of DT on operations management is therefore of great interest. In this research paper, we aim to develop a DT prototype for service-oriented organisations in the retail sector. More specifically, we study the case of implementing a DT in smart stores and assess its impact on daily operations management performances using simulation.